47 An audit of the completeness of the pathological request form for the diagnosis of possible ovarian malignancy in UK tertiary cancer centre. (13th November 2020) - Daas, M; Addley, S; Dhar, S; Soleymani Majd, H; Alazzam, M
Abstract : Introduction: Ovarian cancer prognosis and treatment plan are affected by the accuracy of the pathological report which highly depends on the clinical data. In this Audit, we reviewed the BGCS and The Royal College of Pathology guidelines for reporting ovarian carcinomas recommendation regarding the clinical information required on the pathological request and compare it with the current practice. This audit aims to enhance the pathological request-form of possible ovarian malignancy and increase the adherence of surgeons to the current guidelines. Methods: A retrospective study of consecutive 115 pathological request forms for patients who had undergone debulking surgeries for suspected ovarian malignancy at a tertiary university UK hospital. Pathology records were obtained from the 1st January 2016 until 31st December 2018. Results: 100% of the request forms contained the demographics, site of tumour origin and marked multiple specimens. However, there was no documentation for the clinical presentation, family history of cancers and history of previous hormonal therapy. Implications: Using generic pathology request forms resulted in missing key information which could very helpful to the pathologist in order to provide an accurate diagnosis. Electronic organ-specific pathology forms with dynamic fields must be incorporated into clinical practice for accurate diagnosis and staging. Key information such as clinical presentation, results of previous biopsies, radiological staging if available, and surgery details. Furthermore, add checkboxes for family history of cancers, history of taking any chemotherapy or hormonal replacement therapy.